The dimensions of the electronic spoken word and its role in Strengthen the management of customer expectations : A descriptive analytical study of the opinions of a sample of workers in a number of hotels in the Kurdistan region of Iraq - Omer, Mohammed; Sadiq, Darman (Humanities Journal of University of Zakho, 2023)
The research aims to determine the dimensions of the electronic spoken word and its role in enhancing the management of customer expectations among workers in a number of hotels in the Kurdistan region of Iraq, The research presented a theoretical framework that dealt with the variables of the electronic spoken word as an independent variable, which is represented by its dimensions (the credibility of information, the quality of information, the usefulness of information, and the attitude towards information) and the management of customer expectations as an approved variable, and this prompted the researchers to formulate a number of main hypotheses, and these hypotheses were tested through the use of a set of statistical analytical methods, and 70 questionnaires were distributed to the administrative and authorized leaders in the surveyed hotels and 65 valid forms were retrieved for statistical analysis The research reached a set of conclusions, the most prominent of which were: e-WOM is one of the digital marketing strategies through which the organization will encourage its customers to publish opinions and comments about its hotel services in various digital channels. Among the most important proposals that came out of the research: the researched hotels pay more attention to the comments and opinions of current customers and take advantage of the comments and information provided by them to reach creative solutions that help them to provide in order to provide the best hotel services in the future.